Rethinking the UTS International Studies Degree Post-Covid 19 - Angela Giovanangeli; Lesley Harbon; Alice Loda (PORTAL: Journal of Multidisciplinary International Studies)
The Bachelor of Arts in International Studies (BAIS) at UTS has been reimagined to address the challenges of the Covid-19 pandemic and shifting priorities in higher education. The redesign introduces flexible global mobility options, including virtual experiences and localised intercultural learning, while embedding the Indigenous Graduate Attribute (IGA) across the curriculum. By blending physical, virtual, and local experiences, the program fosters critical reflection and equips students with ethical and professional intercultural skills, ensuring meaningful engagement with both local and global communities.